SOLID WASTE FROM THE PERSPECTIVE OF LAW 12.305/2010: PERSPECTIVES AND ADVANCES IN THE MUNICIPALITY OF ESPIGÃO DO OESTE/RO (REMUNOM, 2025)
This article aims to contextualize Law 12.305/2010 and its legal aspects, as they relate to solid waste. The research was conducted in the municipality of Espigão do Oeste, a municipality in the state of Rondônia that has been struggling to find an alternative to manage the solid waste produced by the municipality. It has instituted the municipal plan for Integrated Management of solid waste, formed a consortium with the municipality of Cacoal for the use of the sanitary landfill and enabled the private sector to recycle all cardboard produced in the municipality. However, it still needs to advance in the management of many solid waste items that contaminate the entrances and exits of the city and the main roads of the municipality.